2008
DOI: 10.1080/10498850802179776
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Germination and Inactivation ofBacillus cereusSpores and Their Survival in Fresh Blue Crab Meat (Callinectes sapidus) During Storage

Abstract: Pressure-induced germination and inactivation of three strains of B. cereus spores by high hydrostatic pressures between 100 and 550 MPa al 40'^C for 15 min was studied. In sterile distilled water, spore germination remained stable with pressures up lo 300 MPa, and increased at pressures between 300 and 500 MPa, with maximum germination and inactivation obtained at 550 MPa. Of the 3 strains, spores from the crabmeat isolate were found to be ihe most resistant to germination and inactivation by pressure. In fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…If spore-forming bacteria are present, they would require more severe pressure/time conditions than vegetative cells for inactivation [ 89 ]. In addition, pressure treatments below 600 MPa may trigger the germination of spore-forming bacteria [ 90 ]. In fact, the presence of spore-forming species with pathogenic potential such as Bacillus weihenstephanensis has been reported in the meat of edible crab [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…If spore-forming bacteria are present, they would require more severe pressure/time conditions than vegetative cells for inactivation [ 89 ]. In addition, pressure treatments below 600 MPa may trigger the germination of spore-forming bacteria [ 90 ]. In fact, the presence of spore-forming species with pathogenic potential such as Bacillus weihenstephanensis has been reported in the meat of edible crab [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spores can germinate into vegetative cells under favorable conditions, such as (but not limited to) mild heat (<80 °C for up to 10 min); low pressure (<300 MPa); and the presence of germinants (alanine, lysine, etc.) [ 14 , 15 , 16 ]. B. cereus spores germinate into vegetative cells, which can produce two types of toxins, either emetic or diarrheal.…”
Section: Food-borne Pathogens and Their Thermal Resistancementioning
confidence: 99%
“…The results here underscore the observation that both spore germination and inactivation occur upon exposure to selected moderate pressure-temperature treatments, as previously reported. [16] Although some researchers have shown B. subtilis spores to be relatively sensitive to high pressure treatment, [17] others have reported that these spores are pressure resistant even if exposed to static pressures as great as 1000 MPa. [7,18,19] In a further demonstration of this phenomenon, Wuytack et al [18] showed that at 40°C B. subtilis germination at 100 MPa resulted in rapid ATP generation; however, ATP generation was nonexistent in cells germinated at 600 MPa.…”
Section: Kinetic Analysis Of B Subtilis Spore Inactivationmentioning
confidence: 99%
“…B. subtilis was chosen as the model microorganism because its endospores are extremely resistant to many sterilization methods. [14][15][16][17][18][19] We report the kinetic parameters that describe the rate of inactivation, that is, D values, the temperature sensitivity parameter (Z T ), and the pressure sensitivity parameter (Z P ).…”
Section: Introductionmentioning
confidence: 99%